2014
DOI: 10.1017/s1743921314013714
|View full text |Cite
|
Sign up to set email alerts
|

A Supervoid Explanation of the Cosmic Microwave Background Cold Spot

Abstract: Abstract. The Cold Spot is an anomalously cold region in the Cosmic Microwave Background (Vielva et al. 2004), either caused by a structure in the line of sight or could be of primordial origin. We search for a supervoid aligned with the Cold Spot region, filling the gap in redshift at z < 0.3 which has never been explored in details. We find a large projected under density in the recently constructed WISE-2MASS catalogue, whose median redshift is z 0.14, with an angular size of 30 degrees. We show that a sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(78 citation statements)
references
References 5 publications
(3 reference statements)
9
68
1
Order By: Relevance
“…More recently, Refs. [78,79] claimed the detection of a supervoid aligned with a prominent cold spot in the Planck CMB maps, as one would expect in models with positive ISW effect.…”
Section: Parameter/datasetmentioning
confidence: 92%
“…More recently, Refs. [78,79] claimed the detection of a supervoid aligned with a prominent cold spot in the Planck CMB maps, as one would expect in models with positive ISW effect.…”
Section: Parameter/datasetmentioning
confidence: 92%
“…A first attempt to understand a possible correlation between these observations was made in Ref. [516], where it was found that a Lemaître-Tolman-Bondi (LTB) void could fit both the Cold Spot and the super-void.…”
Section: Anomaly Detection: a How-to Guidementioning
confidence: 99%
“…The void is aligned with the Cold Spot (CS) in the CMB (Finelli et al 2016), hence we call it the "CS Void." The survey area is 21200 sq.…”
Section: Voidmentioning
confidence: 99%